Restless Legs Syndrome in Chinese Patients With Sporadic Amyotrophic Lateral Sclerosis - Liu, Shuangwu; Shen, Dongchao; Tai, Hongfei; Su, Ning; Ding, Qingyun; Fu, Hanhui; Zhang, Kang; Wang, Zhili; Liu, Mingsheng; Huang, Yan; Cui, Liying (Frontiers in Neurology, 2018)
Objective: To evaluate the frequency and clinical features of restless legs syndrome (RLS) in a group of Chinese patients with amyotrophic lateral sclerosis (ALS). Methods: 109 Patients included in this study fulfilled the revised El Escorial diagnostic criteria for clinically definite, probable and lab-supported probable ALS, and a group of 109 control subjects was matched for age and sex to the ALS group. Disease severity was assessed by the revised ALS functional rating scale (ALSFRS-R). The diagnosis of RLS was made according to the criteria of the International RLS Study Group. Other characteristics including sleep quality, excessive daytime sleepiness (EDS), REM sleep behaviour disorder (RBD), depression and anxiety were also evaluated in ALS patients. Results: RLS was significantly more frequent in ALS patients than in control subjects (14.6% vs. 0.9%; P<0.05). Compared to those without RLS, ALS patients with RLS reported a higher frequency of anxiety and EDS. ALS patients with RLS showed more severe legs dysfunction. EDS and legs function scores of the ALSFRS-R were independent factors significantly associated with RLS in ALS patients. Conclusions: Our findings suggest that Chinese ALS patients exhibit a high frequency of RLS symptoms and that these patients may benefit from recognition of the condition and optimized management of its symptoms. Moreover, ALS patients might cause circadian rhythms disturbance and our study further supports that ALS is a heterogeneous disorder involving multiple systems; further studies are needed to confirm these preliminary findings.